2016
DOI: 10.11114/jets.v4i5.1337
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Foreign Language Classroom Anxiety and Achievement in Foreign Language in Turkish University Students in Terms of Various Variables

Abstract: This correlational survey study aimed to investigate whether the Turkish prep-class students' foreign language classroom anxiety levels and foreign language achievement significantly differ in terms of such variables as their gender, their experience abroad, perceived level of income and any third language (other than Turkish and English) they knew. Moreover, the study also tried to identify whether the sub-dimensions of the foreign language classroom anxiety scalespeaking anxiety in language class, interest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
1
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 40 publications
(52 reference statements)
3
21
1
17
Order By: Relevance
“…It is encountered often in the literature. And, since the preliminary study of Horwitz, Horwitz and Cope (1986) in this respect, many studies (Awan Azher, Anwar, & Naz, 2010;Demirdas & Bozdogan, 2013;Dogan & Tuncer, 2016;Proulx, 1991) have reported this result.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is encountered often in the literature. And, since the preliminary study of Horwitz, Horwitz and Cope (1986) in this respect, many studies (Awan Azher, Anwar, & Naz, 2010;Demirdas & Bozdogan, 2013;Dogan & Tuncer, 2016;Proulx, 1991) have reported this result.…”
Section: Discussionmentioning
confidence: 87%
“…Yet, it was stated that the proficiency levels of learners and gender do not affect language anxiety. Furthermore, Tuncer and Dogan (2016) made a research so as to identify to what extent the Turkish students' English classroom anxiety affects their academic achievement in English language. And, the findings of the study were revealed that the students' anxiety evolving and ever-increasing during their English prep-education powerfully predicted their academic performance.…”
Section: Anxiety and Foreign Language Learningmentioning
confidence: 99%
“…Además, los investigadores no logran llegar a un consenso sobre su categorización y las relaciones entre variables (Dörnyei, 2018;Dörnyei y Ushioda, 2011). A pesar de la falta de consenso, sí existe acuerdo en destacar la ansiedad en el aprendizaje de idiomas o ansiedad idiomática como uno de los elementos relevantes de estudio (Alpaslan y Yalvac, 2017;Asif, 2017;Dogan y Tuncer, 2016;Horwitz, 2010;Ramos, 2017;Razak et al, 2017;Sánchez-Carrón, 2013).…”
Section: Los Factores Afectivos En El Aprendizaje De Idiomasunclassified
“…Dentro de estos factores, un número creciente de docentes e investigadores señalan la ansiedad como la variable con mayor influencia negativa (Alpaslan y Yalvac, 2017;Asif, 2017;Bhatti y Memon, 2016;Dogan y Tuncer, 2016;Ramos, 2017;Razak, Yassin, y Maasum, 2017;Sánchez-Carrón, 2013;Santos, Gorter, y Cenoz, 2017). La ansiedad es un estado psicológico presente en la vida de las personas, con efectos tanto en lo fisiológico como en lo emocional, y que afecta al desempeño profesional y al rendimiento académico.…”
unclassified
See 1 more Smart Citation